Dilemas da inclusão no modelo de formação universitária em ciclos: uma análise das dimensões da efetividade e eficácia da lei nº 12.711/2012 - Silva, Jeferson Santos Teixeira da (Universidade Federal Rural do Semi-Árido, 2018)
How are the dimensions of applicability and effectiveness of Law nº 12.711 / 2012 presented in the model of university graduation in cycles? This paper analyzes the social and legalnormative aspects relevant to this problem. To do so, it starts from a documental and bibliographical analysis and promotes the quantitative and qualitative investigation of the social aspects underlying the dimensions of applicability and effectiveness of the University Quotas Law, through field research that uses as a universe of research the Bachelor of Science and Technology and the courses of engineering linked to them, from a population sample from the Main Campus of the Federal Rural University of the Semi-Arid. Based on the questions asked, it is possible to extract the proportion of quotaters and non-quotators in each step of the cycle, comparisons of their performance, as well as their impressions about the selection model for admission to the second cycle used in UFERSA. Its specific objectives are: (1) to quantitatively investigate the existence of a proportion between the incoming quotaters in the first and second cycles of UFERSA-Mossoró undergraduate courses; (2) to investigate the dimensions of applicability, effectiveness and necessity of Law 12.711/2012 in the cycle graduation model of UFERSA; (3) to investigate quantitatively and qualitatively the student community support to the application of the University Quotas Law in the mechanism of access to the engineering courses from the graduation model in cycles; (4) promote debate among students about the importance, effectiveness, necessity and applicability of the University Quotas Law; (5) present a legal opinion about the possibility of establishing affirmative actions in the selection process for admission to the second cycle of University courses, based on the elements raised in quantitative, qualitative, normative and bibliographic research. It is justified by the need to establish a dialogue between the new subjective and pedagogical paradigms of higher education, in order to obtain a more precise analysis of the applicability and effectiveness dimensions of Law 12.711/2012. It occurs through the inductive method. It reveals the satisfactory performance of the quotaholders in the first cycle of formation, but the existence of such a disadvantage in the process of selection for entry in the subsequent stage, in relation to the non-quotaters. It identifies a large disproportion between quotaters and non-quotaters enrolled in the second cycle courses. It shows the students' acceptance of affirmative actions based on a factor of apparent consequences, to the detriment of those with latent corollaries. It concludes that the obstacle to the applicability of the law in selective competitions destined to holders of diplomas, in this graduation model, can be detrimental to the effectiveness of the University Quotas Law, regarding the achievement of its objectives, pointing to the possibility of implementing affirmative actions in the access to the second cycle as a way to mitigate this incidental exclusion.
Monografia
Keywords: Lei de cotas; Efetividade; Eficácia; Ações afirmativas; Bacharelados interdisciplinares; Quotas law; Applicability; Effectiveness; Affirmative action; Interdisciplinary bachelor's; CIENCIAS SOCIAIS APLICADAS::DIREITO